2020
DOI: 10.1080/1354750x.2020.1725786
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CEA and CA19-9 serum levels independently predict advanced pancreatic cancer at diagnosis

Abstract: Purpose: It is suggested that tumour markers carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) could be used to predict the stage of pancreatic cancer. However, optimal cut-off values for CEA and CA19-9 are disputable. This study aimed to assess the value of CEA and CA19-9 serum levels at diagnosis of pancreatic ductal adenocarcinoma (PDAC) as predictors for the advanced stage of PDAC in patients discussed at pancreatic multidisciplinary team (MDT) meetings. Methods: Patients with suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 43 publications
2
49
1
1
Order By: Relevance
“…Several authors have shown significant elevation of the serum CEA and Ca19-9 tumor markers is associated with metastatic disease and helpful in tailoring diagnostics [ 9 , 10 , 11 ]. This patient's initial CEA was 63.4 ng/ml and Ca 19-9 was 5052 U/ml both markedly elevated, prompting the staging laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown significant elevation of the serum CEA and Ca19-9 tumor markers is associated with metastatic disease and helpful in tailoring diagnostics [ 9 , 10 , 11 ]. This patient's initial CEA was 63.4 ng/ml and Ca 19-9 was 5052 U/ml both markedly elevated, prompting the staging laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported case, we had a borderline pancreatic tumor due to partial occlusion of the lumen of the superior mesenteric vein[ 14 ]. The normality of the tested markers, correlated to imaging tests, suggested the absence of a systemically advanced disease and good chances of resectability[ 15 , 16 ], mainly in association with neoadjuvant treatment. However, liver metastasis was not found on imaging, being detected only at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CA19-9 and CEA were considered elevated if above 27 kU/L or 3 µg/L, respectively, according to the laboratory cut-off values commonly used in our center. Moreover, other clinically relevant cut-off values, CEA>7 µg/L and CA19-9>305 kU/L, as recently detected by our group, were also used in the analyses as well as combined cut-off values [ 14 ].…”
Section: Methodsmentioning
confidence: 99%